Insertion of the environment theme in teaching by graduated teachers for UFPR Litoral: An analysis from the Theory of Planned Behavior - Alano, Elsi do Rocio Cardoso; Oliveira, Adriana Lucinda de; Joucoski, Emerson; Pereira, Gabriela Santos; Martins, Aline Hagedorn Vallejo; Martins, Maria Lúcia de Souza; Trizoti, Eduarda Pedrotti (Seven Editora, 2023)
The research is supposed to investigate the factors that influence the behavioral intention of the teacher (a) egress (a) of the Coastal Sector of UFPR, in the adoption of the theme environment as a teaching practice in their classes, being this transversal theme necessary and important in view of the environmental issues in teaching at its various levels. The Theory of Planned Behavior (TPB), a theory developed by Ajzen (1991), was applied in the educational context, more precisely in teaching, whose sample comprises 64 graduates of UFPR Litoral, who were teachers at the time they answered the questionnaire online of the survey, being an integral part of the respondents of the survey of the Education and Work Group, which has a total of 470 respondents until the year 2019. Of these 64 respondents, 59 include the theme Environment in education, regardless of the area of training. The results show that there are some characteristics that drive this pedagogical practice. It should be emphasized that the research is under development by the Education and Work group of UFPR Litoral. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-063